The Risk of Hypertension and Other Chronic Diseases: Comparing Smokeless Tobacco with Smoking - Ankit Anand; Md Illias Kanchan Sk (Frontiers Media S.A., 2017)
BackgroundIn the past, studies have compared smokeless tobacco and non-tobacco users for the risk of various chronic diseases. The differences in the risk of chronic diseases between smokeless tobacco user and smokers have not been explored. The objective of this study is to estimate the risk of chronic diseases among smokeless tobacco users compared to smokers.MethodsThe data were used from the Study on Global Ageing and Adult Health (SAGE) Wave-1, conducted in 2007-2008 in India. The study sample is the respondents who reported consuming any form of tobacco in last 1 month. The total sample size was 4,038 respondents. The odds ratio of chronic morbidities was estimated taking smokers as the reference category.ResultsThe odds ratios for (self-reported) diabetes, asthma, and hypertension were not significant for smokeless tobacco user compared to smoked tobacco users. The odds ratio of chronic lung diseases (CLDs) was significantly lower among smokeless tobacco users compared to smoked tobacco users. The odds ratio of hypertension (measured) combined with low education and belonging to lowest wealth quintiles were not significant for smokeless tobacco users compared to smoked tobacco users. Duration of the use of smokeless tobacco and quantity of use was found to have no significant relation with risk of chronic diseases as compared to smoking.ConclusionThis study did not find the significantly higher risk of chronic morbidities except for CLD for smokeless tobacco users compared to smoked tobacco users. The study suggests that the use of any form of tobacco may have a similar risk of chronic diseases.